2022
DOI: 10.2298/jsc210520050a
|View full text |Cite
|
Sign up to set email alerts
|

Electrocatalytic hydrogen evolution upon reduction of pyridoxal semicarbazone and thiosemicarbazone-based Cu(II) complexes

Abstract: The growing global demand for renewable energy sources has pushed renewable, green energy sources to the forefront, among which the production of hydrogen gas from water occupies a significant place. To realize this goal, researchers across the globe are developing various systems that could swiftly catalyse the hydrogen evolution reaction (HER) in the highest possible yield. In the present work, we report electrocatalytic HER performances of pyridoxal semicarbazone- and thiosemicarbazone-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…The complexes have shown promising antitumor, antiviral, and inflammatory activities, in some cases higher than that of cisplatin [15]. Their pote use as materials for electrocatalytic hydrogen evolution has also been proven [16] second largest group of PLITSC-containing compounds has iron as a central metal io in Fe(PLITSC)Cl3 × H2O, Fe(PLITSC)(PLITSC-H)](NO3)2 × H2O, [Fe(PLITSC)(PLIT H)]SO4 × 2H2O [14], Fe(PLITSC)Cl3 × H2O, Fe(PLITSC)(PLITSC-H)](NO3)2 × H2O, [Fe(PLITSC)(PLITSC-H)]SO4 × 2H2O [9]. Cobalt, nickel, and other metal ions also e coordinate with the mentioned ligand, some examples are Co(PLITSC-2H)(PLITSC-CH3OH [17];…”
Section: Scheme 1 Synthesis Of Pyridoxal-isothiosemicarbazone (Plitsc)mentioning
confidence: 99%
See 2 more Smart Citations
“…The complexes have shown promising antitumor, antiviral, and inflammatory activities, in some cases higher than that of cisplatin [15]. Their pote use as materials for electrocatalytic hydrogen evolution has also been proven [16] second largest group of PLITSC-containing compounds has iron as a central metal io in Fe(PLITSC)Cl3 × H2O, Fe(PLITSC)(PLITSC-H)](NO3)2 × H2O, [Fe(PLITSC)(PLIT H)]SO4 × 2H2O [14], Fe(PLITSC)Cl3 × H2O, Fe(PLITSC)(PLITSC-H)](NO3)2 × H2O, [Fe(PLITSC)(PLITSC-H)]SO4 × 2H2O [9]. Cobalt, nickel, and other metal ions also e coordinate with the mentioned ligand, some examples are Co(PLITSC-2H)(PLITSC-CH3OH [17];…”
Section: Scheme 1 Synthesis Of Pyridoxal-isothiosemicarbazone (Plitsc)mentioning
confidence: 99%
“…[Co(PLITSC-H)2]BrNO3×CH3OH [18], Co [20]. Over the past decade good catalytic properties of transition metal complexes with derivatives of pyrid carbazone as ligands have been studied [16,[21][22][23][24][25].…”
Section: Scheme 1 Synthesis Of Pyridoxal-isothiosemicarbazone (Plitsc)mentioning
confidence: 99%
See 1 more Smart Citation
“…The coordination compounds with CuII are interesting because of the biological relevance of copper as an essential ion and antiviral, antitumor, and anti-inflammatory activity of these systems [ 15 ]. It has been shown that Cu complexes with pyridoxal semicarbazones and PLITSC can be used as a promising material for electrocatalytic hydrogen evolution [ 16 ]. The Cu complexes with morpholine–thiosemicarbazone hybrids specifically inhibited the growth of S. aureus with MIC value of 2–5 μg mL −1 and accumulated in the cancer cells through ribonucleotide reductase inhibition [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The Zn and Cu complexes of the same ligand manifested high antibacterial activity [ 27 ]. In the last decade, several papers describing the good catalytic properties of the transition metal complexes with pyridoxal-carbazone [ 16 , 28 , 29 , 30 , 31 , 32 , 33 ] have been published.…”
Section: Introductionmentioning
confidence: 99%